Strategi Guru dalam Penerapan Metode Bisik Berantai Untuk Keterampilan Menyimak dalam Pembelajaran Bahasa Indonesia di Kelas IV SDN 195 Pematang Kancil - M. Febri Afsan; Risma Anggreyani; Syafrida Dwi Hestiana; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to describe the application of the whisper-chain method to listening skills in Indonesian language learning in elementary schools and the factors that influence it. This research is a qualitative research. This research is a literature study, namely research that examines research journals and other sources related to improving listening skills by using the whisper chain method based on the field in the journal article. The data in this study were obtained from research results on the topic of the whisper-chain method in improving listening skills in elementary schools in Indonesia which have been published in various online journals indexed by Google Scholar. The number of journals obtained is 3 research journals that have been selected according to the research topic. Based on the results of a journal review consisting of 3 journals studied in the form of classroom action research and qualitative from 2013 to 2016 it can be concluded that the application of the whisper-chain method for listening skills in Indonesian language learning, that what the teacher did was in accordance with the learning procedures but in terms of material selection is not in accordance with the material characteristics of the chain whisper method. The influencing factors are the objective factor, the students' interest and attention, the condition situation, facilities or infrastructure, the teacher which includes the teacher's educational background and teaching skills.